Assessing the Visitor and Animal Outcomes of a Zoo Encounter and Guided Tour Program with Ambassador Cheetahs. (4th March 2022) - Whitehouse-Tedd, Katherine M.; Lozano-Martinez, Jairo; Reeves, Jessica; Page, Mollie; Martin, Jaime H.; Prozesky, Heidi
ABSTRACT: Research into the effectiveness of zoo Ambassador Animal Programs (AAPs) has typically investigated human or animal factors separately. This study took a multi-dimensional approach and aimed primarily to (1) determine whether change in visitor knowledge was influenced by the type of experience undertaken and (2) assess welfare indicators in ambassador cheetahs ( Acinonyx jubatus ) during encounter and non-encounter periods at a South African zoological facility. The AAP was evaluated for its visitor impact using a repeated-measures study design, whereby visitor agreement with six statements (3 being correct and 3 being incorrect) were assessed pre- and post-visit; change in responses was then compared according to the type of visit (encounter, guided tour, or combination; n = 182). Behavioral indicators (activity budget, pacing, lying with head down, and behaviors indicative of positive [purring] or negative [tail-flicking] affective states) were measured as well as a physiological (heart rate) indicator of animal welfare for cheetahs ( n = 5). The expression of these indicators was compared according to whether the cheetahs were on display (with and without visitor presence at the fence) and involved in an encounter (with and without physical interaction, that is, being stroked). A positive knowledge change was recorded in 62% of visitors, regardless of experience type, whilst 11% and 27% exhibited no change or reduced knowledge score, respectively. Visitors involved in encounters had a significantly lower (but still positive) knowledge change compared with other visit types. No difference in cheetah behavior was detected for interaction and non-interaction periods. However, cheetahs spent greater periods of time lying with their head down whilst being stroked, and the mean heart rate was significantly lower during these interactions. These findings indicate that animal–visitor encounters alone are unlikely to promote conservation-education, but the addition of a guided tour was important in facilitating increased conservation-education. Whilst the welfare of animal ambassadors was not compromised by visitor encounters, negative changes in knowledge scores for some visitors suggest areas for improvement exist.